Fault zone controlled seafloor methane seepage in the rupture area of the 2010 Maule earthquake, Central Chile. (30th November 2016) - Geersen, Jacob; Scholz, Florian; Linke, Peter; Schmidt, Mark; Lange, Dietrich; Behrmann, Jan H.; Völker, David; Hensen, Christian
Abstract: Seafloor seepage of hydrocarbon‐bearing fluids has been identified in a number of marine fore arcs. However, temporal variations in seep activity and the structural and tectonic parameters that control the seepage often remain poorly constrained. Subduction zone earthquakes, for example, are often discussed to trigger seafloor seepage but causal links that go beyond theoretical considerations have not yet been fully established. This is mainly due to the inaccessibility of offshore epicentral areas, the infrequent occurrence of large earthquakes, and challenges associated with offshore monitoring of seepage over large areas and sufficient time periods. Here we report visual, geochemical, geophysical, and modeling results and observations from the Concepción Methane Seep Area (offshore Central Chile) located in the rupture area of the 2010 Mw. 8.8 Maule earthquake. High methane concentrations in the oceanic water column and a shallow subbottom depth of sulfate penetration indicate active methane seepage. The stable carbon isotope signature of the methane and hydrocarbon composition of the released gas indicate a mixture of shallow‐sourced biogenic gas and a deeper sourced thermogenic component. Pristine fissures and fractures observed at the seafloor together with seismically imaged large faults in the marine fore arc may represent effective pathways for methane migration. Upper plate fault activity with hydraulic fracturing and dilation is in line with increased normal Coulomb stress during large plate‐boundary earthquakes, as exemplarily modeled for the 2010 earthquake. On a global perspective our results point out the possible role of recurring large subduction zone earthquakes in driving hydrocarbon seepage from marine fore arcs over long timescales. Key Points: We present manifold evidence for active seafloor methane seepage in the rupture area of the 2010 Maule earthquake, Central Chile Methane seepage is spatially governed by large upper plate faults that crop out at the upper continental slope Recurring plate‐boundary earthquakes enhance fault zone permeability, and thus seafloor seepage, over multiple seismic cycles